STRUKTUR ORGANISASI - M. Zakaria; Liza Audya; Sukatin Sukatin; Zulqarnain Zulqarnain (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2026)
ABSTRACT Studies on organizational structure have predominantly focused on administrative and managerial aspects, while its integration with the perspective of organizational psychology, particularly in Islamic educational institutions, remains insufficiently explored. This gap highlights the need to examine organizational structure not only as a managerial framework but also as a determinant of organizational effectiveness and employee behavior. This study aims to analyze organizational structure from the perspective of organizational psychology and to explain its relevance to the management of Islamic educational institutions. The research employed a qualitative approach using a library research method through a comprehensive review of scholarly books, journal articles, and other relevant academic sources. The findings reveal that organizational structure is built upon six key elements: job specialization, departmentalization, chain of command, span of control, centralization or decentralization, and formalization. These structural elements influence communication patterns, work motivation, job satisfaction, and organizational effectiveness. In the context of Islamic educational institutions, an organizational structure grounded in the principles of tawhid, amanah, shura, and justice contributes to adaptive governance, enhances organizational effectiveness, and supports the development of competent human resources with strong Islamic values. ABSTRAK Kajian mengenai struktur organisasi umumnya masih berfokus pada aspek administratif dan manajerial, sedangkan integrasinya dengan perspektif psikologi organisasi dalam konteks lembaga pendidikan Islam belum banyak dibahas secara komprehensif. Kesenjangan tersebut mendorong pentingnya penelitian ini untuk menganalisis struktur organisasi sebagai faktor yang memengaruhi efektivitas organisasi sekaligus perilaku anggotanya. Penelitian ini bertujuan menganalisis struktur organisasi dalam perspektif psikologi organisasi serta menjelaskan relevansinya bagi pengelolaan lembaga pendidikan Islam. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan melalui penelaahan berbagai buku, artikel ilmiah, dan hasil penelitian yang relevan. Hasil kajian menunjukkan bahwa struktur organisasi dibangun oleh enam elemen utama, yaitu spesialisasi pekerjaan, departementalisasi, rantai komando, rentang kendali, sentralisasi atau desentralisasi, dan formalisasi. Konfigurasi elemen tersebut memengaruhi pola komunikasi, motivasi, kepuasan kerja, dan efektivitas organisasi. Dalam lembaga pendidikan Islam, struktur organisasi yang berlandaskan nilai tauhid, amanah, syura, dan keadilan mampu mendukung tata kelola yang adaptif, meningkatkan efektivitas organisasi, serta memperkuat pengembangan sumber daya manusia yang profesional dan berkarakter Islami.